Penghijauan Sebagai Upaya Pelestarian Lingkungan dan Pemberdayaan Masyarakat - Nur Elsa Choiru Ummah; Eli Masnawati; Yeni Vitrianingsih; Mujito Mujito; Didit Darmawan; Adi Herisasono; Suwito Suwito (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Important conceptual activities are carried out to deal with the environmental crisis by preserving the environment through reforestation. The condition of developing areas and the changing function of space for development requires the concept of greening. Humans are one of the determining factors for efforts to preserve the environment while having the role and responsibility of empowering environmental wealth for the survival of the ecosystem. The purpose of this community service activity is to revive natural aesthetics, trees as air fresheners, and flood mitigation. Community service with greening efforts to preserve the environment uses the Participatory Action Research (PAR) method as a basis. The results obtained include the creation of a fresh, healthy, and cool atmosphere, nature becomes maintained and clean, and the addition of new knowledge to do reforestation through planting tree seedlings.